Odpowiedź:
a)
y = -4x²-3x+ 7
a = - 4, b = - 3 , c = 7
Δ= b²- 4ac = (-3)² - 4 * ( -4) * 7 = 9 + 112 = 121
√Δ = √121 = 11
x₁= (-b - √Δ)/2a = (3 - 11)/(- 8) = - 8/(- 8)= 8/8 = 1
x₂ = ( - b + √Δ)/2a = (3 + 11)/(- 8)= 14/(- 8) = - 14/8 = - 1 6/8 = - 1 3/4
Postać iloczynowa
y = a(x - x₁)(x - x₂) = - 4(x - 1 )(x + 1 3/4)
b)
y = 2x - 3 - x² = - x² + 2x - 3
a = - 1 , b = 2 , c = - 3
Δ= b²- 4ac = 2² - 4 * (- 1) * (- 3) = 4 - 12 = - 8
Ponieważ Δ < 0 , więc funkcja nie ma miejsc zerowych i nie ma postaci iloczynowej